Symposia on Plant (Protein) Phosphorylation - De Vries, Sacco C. (Frontiers in Plant Science, 2012)
From September 14-16, 2011 the twelfth symposium on Plant Protein Phosphorylation was held in Tübingen, Germany. The topic is as broad as the name suggests and covers all aspects of this important means of protein modification in plants. I have had the pleasure of attending the 2007 and the 2011 symposia. The interesting concept behind these meetings is to hear about the same biochemical mechanism operative in a multitude of experimental systems. The meetings are quite informal and present an excellent mix ranging from technology to biochemical experience and novel findings and tools. The two-and-a-half-day program was divided into five double sessions: biotic interactions, hormone signaling, abiotic interactions, Mitogen Activated Protein Kinase (MAPK) and Ca++ pathways and phosphoproteomics. It was hosted by the Zentrum für Molekularbiologie der Pflanzen (ZMBP) and the organizing committee chaired by Klaus Harter.